Synthesis and Evaluation of 1-Methylimidazole Modified-Functional Polymer Stationary Phase - Tian, M.; Row, H.S.; Yan, H.; Row, K.H. (Asian Journal of Chemistry, 2010)
In order to improve the selectivity of the stationary phase of high-performance liquid chromatography (HPLC) columns, functional polymers as new separation media have seen an increasing attention, but it limited by the low column efficiency. Chemical modified polymer has shown tremendous success to increase the efficiency of the column. In this research 1-methylimidazolemodified- functional polymer was synthesized and the characteristic was investigated by FT-IR. Two xanthine derivatives (caffeine and theophylline) were used to evaluate the separation characteristics of the modified polymer stationary phase. Under the optimum mobile phase: acetonitrile/ water (50:50, v/v), the two compounds can obtain better resolution (R = 3.01) on modified polymer column than resolution (R < 1.0) on blank column. The modified polymer as the stationary phase exhibited higher separation efficiency and it was a potential tool for future HPLC separation in environmental and biochemical fields.